Bioactivity Screening of the Selected Turkish Marine Sponges and Three Compounds from Agelas oroides - Orhan, Ilkay Erdogan; Ozcelik, Berrin; Konuklugil, Belma; Putz, Annika; Kaban, Ulku Gokcen; Proksch, Peter (Acg Publications, 2012)
The extracts of various marine sponges (Agelas oroides and Axinella damicornis, Axinella cannabina, Ircinia spinulosa, I. fasciculata, and I. variabilis, Dysidea avara, and Sarcotragus spinulosus) collected from different spots of the Turkish cost of the Mediterranean Sea have been evaluated for their antibacterial, antifungal, 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging, and acetylcholinesterase (AChE) inhibitory activities. Three compounds (oroidin, 4,5-dibromopyrrol-2-carboxylic acid, and 25-hydroxy-24-methylcholesterol) were isolated from A. oroides and tested in the same manner. The sponge extracts showed notable antimicrobial and anti-AChE activity and low DPPH scavenging activity. Oroidin was found to have moderate anti-AChE and strong radical scavenging activities. The results demonstrated that the sponge extracts exerted a variable degree of antibacterial, anti-radical, and anti-AChE activity, whereas they seemed to have similar antifungal effect. Our findings point out to the fact that the collection site has an important influence on bioactivity of the sponges.
Keywords: Marine sponge; antimicrobial; anticholinesterase; radical scavenger; collection site